2023
DOI: 10.52131/pjhss.2023.1102.0500
|View full text |Cite
|
Sign up to set email alerts
|

Self-Regulation and Cognitive Emotion Regulation among Adolescents

Abstract: The present correlational study aimed to examine the relationship between self-regulation and cognitive emotion regulation strategies in adolescents. A sample of 718 adolescents, comprising both boys and girls, from public and private educational institutes in Faisalabad, was conveniently selected for analysis. The participants completed the Adolescents Self-Regulation Inventory (ASRI) and Cognitive Emotion Regulation Questionnaire (CERQ). A significant but negative relationship with one maladaptive cognitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
1
0
Order By: Relevance
“…Adolescents who used short-term self-regulation skills were observed to have lower levels of adaptive coping, often using catastrophizing, self-blame strategies etc. 40 Bhave et al, 6 also found that emotional intelligence was positively correlated with short-term and long-term self-regulation in engineering students aged between 17 to 18 years. They also suggested that interventions should target enhancement of self-regulation in adolescents.…”
Section: Relationship Between Total and Subscores Of Asri And Tobacco...mentioning
confidence: 95%
“…Adolescents who used short-term self-regulation skills were observed to have lower levels of adaptive coping, often using catastrophizing, self-blame strategies etc. 40 Bhave et al, 6 also found that emotional intelligence was positively correlated with short-term and long-term self-regulation in engineering students aged between 17 to 18 years. They also suggested that interventions should target enhancement of self-regulation in adolescents.…”
Section: Relationship Between Total and Subscores Of Asri And Tobacco...mentioning
confidence: 95%
“…Therefore, for satisfactory self-regulation of emotion, the use of complex cognitive domains like CERS are necessary (Silvers et al, 2012). In their recent research, Khawar et al (2023) delved into the relationship between self-regulation and cognitive emotion regulation in adolescents. The findings from their study showed that self-regulation abilities are a significant negative predictor of other-blame (maladaptive CERS).…”
Section: Attachment and Emotion Regulationmentioning
confidence: 99%